The function of the speeches in the Acts of the Apostles : a key to interpretation of Luke's use of speeches in Acts - Kucicki, Janusz, 1967- (Biblical Interpretation Series, 2017)
In The Function of the Speeches in the Acts of the Apostles , Janusz Kucicki offers a new approach to interpretation of speeches contained in the Acts of the Apostles. He separated all speeches from the narrative parts of Acts and analyze them independently. Without narrative contexts the speeches expose their interrelation that allow to categorize the speeches into two major groups. The first group named \'the topic speeches\' contains the speeches, which create the topic group with common theme that is developed within the three speeches, where the first takes introductory character, the second takes the progressive character and the third takes the conclusive character. The second group of speeches named "the structural speeches" contains the speeches without developed theme.